Synthesis and biological evaluation of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-phenylthiazole derivatives - Shinde, Vikas; Mhaske, Pravin C.; Singh, Aakriti; Sarkar, Dhiman; Mahulikar, Pramod (Journal of Heterocyclic Chemistry, 2019)
A novel series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-substitutedthiazole derivatives (8a-l) have been synthesized by [3 + 2] cycloaddition reaction of 4-(4-ethynylphenyl)-2-substitutedthiazole with substituted benzyl azide in aqueous DMF. Starting compounds 4-(4-ethynylphenyl)-2-substitutedthiazole (6a-d) were synthesized by reaction of 4-(2-substitutedthiazol-4-yl)benzaldehyde with Ohira-Bestmann reagent in methanol. The structures of these novel triazole-thiazole clubbed derivatives were confirmed by the spectral analysis. The title compounds (8a-l) were tested for antimycobacterial activity against Mycobacterium tuberculosis H37Ra active and dormant (MTB, ATCC 25177) and antimicrobial activity against standard Gram-positive bacteria, Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162), and Gram-negative bacteria, Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059). Compounds 8a, 8b, 8c, and 8h reported good activity against B subtilis, compounds 8a, 8b, and 8c showed good activity against S aureus, and compound 8b showed good activity against dormant M tuberculosis H37Rv strain. Compounds 8b and 8c found more potent against Gram positive and dormant M tuberculosis H37Rv strains. These novel triazole-thiazole clubbed analogues found to be a capable leads for further optimization and development.